IMPLEMENTASI PERATURAN DAERAH NOMOR 12 TAHUN 2012 TENTANG RENCANA PEMBANGUNAN JANGKA MENENGAH DAERAH KABUPATEN KAMPAR DALAM MENINGKATKAN EKONOMI KERAKYATAN - Harapan Tua R.F.S, Santri Imam, Meyzi Heriyanto, (Jurnal Ilmu Administrasi Negara, 2020)
Implementation of Regional Regulation No. 12 of 2012 concerning the Medium-Term Development Plan of the Kampar District in Improving Community Economy. The purpose of this study was to determine the implementation of Regional Regulation No. 12 of 2012 concerning the Kampar Regency Regional Medium-Term Development Plan in improving the people’s economy in the Kampar Kiri Hilir Sub-District Management Unit and the inhibiting factors in the implementation of Regional Regulation No. 12 of 2012 concerning the Medium-Term Development Plan Kampar District in improving the people’s economy in the Unit of Management of the One-Day Activities of the Kampar District of Hilir Kiri. The results showed that the implementation of Local Regulation Number 12 of 2012 regarding the Kampar Regency Regional Medium-Term Development Plan in improving the people’s economy in the Kampar Kiri Hilir District of the One-day Activity Management Unit there are several factors that must be considered yatu communication, resources, disposition and bureaucratic structure.